Cinza vegetal e manejos de aplicação na implantação e manutenção de pastagem de Urochloa brizantha no cerrado mato-grossense - Simeon, Bency G. (2020)
The growth and proper management of forage plants represent a basis for the implementation of efficient farm animals’ production systems. In this sense, the Urochloa brizantha (Hochst. Ex A. Rich.) R.D. Webster cv. BRS Paiaguás presents an important alternative for the production of forage in the Brazilian Cerrado. Thus, the objective of this study was to evaluate the use of wood ash in two forms of application (incorporated and not incorporated into the soil), as fertilizer and soil correction in Paiaguás grass pasture in Cerrado MatoGrossense. The experiment was carried out in the field, at the Federal University of Mato Grosso, Rondonópolis campus. The design used was complete randomized blocks, with four replications, in a 5 x 2 factorial scheme, corresponding to five doses of wood ash: 0; 8; 16; 24 and 32 t ha-1 , which comprised the main plots (6 x 12 m), and two forms of application (wood ash incorporated and not incorporated into the soil), which corresponded to the subplots (6 x 6 m), which were arranged banded. Three cuts from the pasture were realized in the years of implantation and maintenance for evaluating the forage grass and soil, in the first and second year of conducting the experiment. In each harvest, soil attributes, soil cover, SPAD, plant height (cm), number of leaves, number of tillers, leaf area index (IAF), leaf / stem ratio, dry leaf mass ( t ha-1 ), dry stem mass (t ha-1 ), root dry mass (t ha-1 ) production and dry mass (t ha1 ). The data were submitted to analysis of variance and regression (p≤0.05). The best results regarding the development of pasture in the year of implantation were: greater height in the third cut 90.78 cm in the incorporated form and in the dose of 24.62 t ha-1 and 87.91 cm in the form not incorporated in the dose of 20.07 t ha-1 ) and forage production of 8,15,10,63 and 7,39 t MS ha-1 , successively in the three cuts, with the incorporation of wood ash into the soil between doses of 16 to 24 t ha-1 . In the second year (maintenance period), dry matter production was 7.46, 7.30 and 12.76 t MS ha-1 , between doses of 20 and 25 t ha-1 . Wood ash increased the dry mass production of Paiaguás grass and its incorporation increased the soil pH from 3.7 in the control dose to 6.66 in the 32 t ha-1 dose in the first 30 days of the year of implantation of the experiment. Wood ash can be considered a source of nutrients for forage grasses and a more economical alternative for correcting soil acidity in the savannah of Mato Grosso.